Is Occult Obscure Gastrointestinal Bleeding a Definite Indication for Capsule Endoscopy? A Retrospective Analysis of Diagnostic Yield in Patients with Occult versus Overt Bleeding. (12th November 2013) - Watari, Ikue; Oka, Shiro; Tanaka, Shinji; Nakano, Makoto; Aoyama, Taiki; Yoshida, Shigeto; Chayama, Kazuaki
Abstract : Background/Aim . Usefulness of capsule endoscopy (CE) for diagnosing small-bowel lesions in patients with obscure gastrointestinal bleeding (OGIB) has been reported. Most reports have addressed the clinical features of overt OGIB, with few addressing occult OGIB. We aimed to clarify whether occult OGIB is a definite indication for CE. Methods . We retrospectively compared the cases of 102 patients with occult OGIB and 325 patients with overt OGIB, all having undergone CE. The diagnostic yield of CE and identification of various lesion types were determined in cases of occult OGIB versus overt OGIB. Results . There was no significant difference in diagnostic yield between occult and overt OGIB. The small-bowel lesions in cases of occult OGIB were diagnosed as ulcer/erosive lesions (n = 18, 18%), vascular lesions (n = 11, 11%), and tumors (n = 4, 3%), and those in cases of overt OGIB were diagnosed as ulcer/erosive lesions (n = 51, 16%), vascular lesions (n = 31, 10%), and tumors (n = 20, 6%). Conclusion . CE detection rates and CE identification of various small-bowel diseases do not differ between patients with occult versus overt OGIB. CE should be actively performed for patients with either occult or overt OGIB.